Percutaneous right ventricle outflow tract stenting in a patient with trisomy 18 associated with double outlet right ventricle - Erkut Öztürk; Ender Ödemiş; Neslihan Kıplapınar (KARE Publishing, 2013)
Trisomy 18, or Edwards syndrome, is the second most common chromosome anomaly after trisomy 21. Various types of congenital heart diseases are seen in the majority of trisomy 18 patients. Palliative treatment of right ventricular outflow tract (RVOT) stenosis includes options like balloon dilatation, stenting and surgery. Herein, we present a case with trisomy 18 and double outlet right ventricle, pulmonary stenosis, and ventricular septal defect. During the follow-up, at the age of three months, his saturation dropped to 70% and an interventional procedure was planned. The patient was considered high risk, and after discussing treatment options with the family, RVOT stenting was chosen. The patient was lost on the 8th day of the follow-up.